Kajian Etnobiologi Tumbuhan dan Hewan yang digunakan dalam Ritual Adat Suku Rejang di Desa Talang Rasau, Kabupaten Rejang Lebong, Bengkulu - Kasrina; Emis Sapitri; Yennita; Irwandi Ansori; Neni Murniati (Jurnal Biosilampari : Jurnal Biologi, 2026)
This study aimed to describe the plant and animal species utilized in the traditional rituals of the Rejang ethnic community and to calculate their Use Value (UV) indices. The research employed both qualitative and quantitative approaches. Qualitative data were collected through participant observation, in-depth interviews, and literature review. Respondents were selected using a purposive sampling method, while quantitative data were analyzed using the Use Value (UV) index to determine the relative importance of each species. The results showed that the Rejang community in Talang Rasau Village utilizes 24 plant species belonging to 17 families and 2 animal species belonging to 2 families in their traditional rituals. The plant species with the highest utilization were coconut (Cocos nucifera L.) and sedingin (Kalanchoe laciniata L.), each being used in 3 out of 6 traditional rituals and having a Use Value (UV) of 0.5. Among the animal species, goat (Capra aegagrus hircus) had the highest utilization, being used in 3 out of 6 traditional ritual activities with a Use Value (UV) of 0.5. These findings confirm that the frequency of a species’ use in traditional rituals is directly proportional to its Use Value, indicating that species used more frequently tend to have higher UV scores.